Screening for Acyl Carrier Protein (ACP) Gene of Oil Palm (Elaeis Quineensia) Using a Synthetic ACP DNA Probe - Abd. Manaf, Mohamad Arif (1994)
Ac DNA library was con structed inphagemid vector pT7T3 using messenger RNA (mRNA) extracted from IS - weekoil palm me socarp as template. The cDNA inserts were detected from agarose gel analysis and ranged in length from 130 to 1300 base pairs.This library was screened with a synthetic ACP probe.Of the 2,000 clones screened using colony hybridisation analysis, 550 clones which gave high intensity of signal were then further screened using phagemid blot hybridisation analysis. This met hodyielded 184 clones which showed a high intensity of signal. The phagemids from the seclones were then screened by Southern hybridisation analysis using a synthetic ACP DNA probe.